A ecological study of galamsey activities in Ghana and their physiological toxicity - Ofori, Samuel Ayetibo; Dwomoh, Joshua; Yeboah, Enoch Owusu; Aggrey, Martin Leo; Nti, Samuel; Philip, Amankwah; Asante, Clement (Asian Journal of Toxicology, Environmental, and Occupational Health, 2024)
Background: Small-Scale Small-Scale Gold Mining (ASGM), locally known as "galamsey," has emerged as a pervasive issue in Ghana characterized with environmental degradation, land and water resource depletion, health hazards for miners, social and economic impacts. This comprehensive review explores the ecological and health effects of galamsey operations across different regions of the country. Methods: The study employs a systematic analysis method to examine the available literature from 2000 to 2023. Various academic databases, including PubMed, Google Scholar, JSTOR, and relevant government publications, were searched to gather relevant information. Findings: The review reveals that galamsey has had significant ecological consequences, including deforestation, habitat destruction, water pollution, and soil degradation, which have adversely affected Ghana's natural beauty. Moreover, the study highlights the physiological health issues faced by galamsey miners, such as accidents, physical strain, mental strain, kidney problems, respiratory disorders, and metabolic diseases. The presence of elevated levels of mercury, cyanide, arsenic, and cadmium in both the environment and the human body are directly linked to ASGM in Ghana. About seventy percent (70%) of the houses in ASGM community relied on surface water, and all of the homes utilized the fields or bush as their main toilet. Conclusion: Implementing remote sensing, geospatial technologies, promoting clean mining technologies, integrating environmental conservation, occupational safety and public health awareness are key technical and innovative measures to mitigate galamsey in Ghana. Novelty/Originality of this article: This study proposes an integrated approach to address the impacts of galamsey, combining remote sensing and geospatial technologies with public health and environmental conservation programs. The model can provide a comprehensive understanding of the spatial and temporal impacts of ASGM and enable more targeted interventions.